Educational Breakout and Sustainable CLIL Teacher Training - Polyakova, O.; de Ros Cócera, L. (Psihologičeskaâ nauka i obrazovanie, 2022)
Abstract only This paper analyses how new learning approaches based on gamification can be used for professional growth in teacher training seminars. To address this matter, we designed and implemented a Breakout Edu competition — a sequence of game-based tasks mixing up education and entertainment. The pilot study involved fifteen plurilingual educators tackling the efficacy of social and cognitive groundworks of collaborative learning through gamification. It is important to highlight that the participants were also experts in teaching non-linguistic subjects in English (Content and Language Integrated Learning or CLIL methodology). The researchers designed and implemented a methodological plan to ensure the process feasibility and confirm the motivational value of the training set. The project comprised the experimental part (workshop, training materials), feedback (questionnaire, discussion), analysis and dissemination of the results. Our results based on an original questionnaire showed a general acceptance of new gamified knowledge building and raised awareness of active learning techniques. Overall, 80% of participants fully agreed with the possibility of implementing this technique in the classroom with the students across different educational stages; the same number of educators considered that the Breakout Edu workshop fully encouraged motivation and teamwork. Despite certain limitations in terms of sample size, our experiment strengthens the dissemination of learner-focused approaches. Profiling professional development challenges of future CLIL instructors was aligned with sustainable development goal 4 (General Assembly Resolution). Research findings will deserve careful thought by the education community, policymakers and teacher-trainers currently promoting CLIL, active learning methodologies and gamification. Целью настоящего исследования является изучение вклада новых подходов к обучению, основанных на геймификации, и их применение для профессионального развития на семинарах по подготовке учителей. Для решения этой задачи мы разработали и внедрили Breakout Edu — последовательность игровых заданий, совмещающих обучение и развлечение. В пилотном исследовании приняли участие пятнадцать полилингвальных педагогов, проверивших эффективность социальных и когнитивных основ совместного обучения с помощью геймификации. Важно отметить, что участники проекта также являются экспертами в преподавании неязыковых предметов на английском языке (методология «Content and Language Integrated Learning — CLIL»). Исследователи разработали и реализовали методический план, призванный обеспечить реализуемость процесса и подтвердить мотивационную ценность учебного комплекса. Проект включал экспериментальную часть (семинар, учебные материалы), обратную связь (анкетирование, обсуждение), анализ и распространение результатов. Данные, полученные с помощью авторского опросника, продемонстрировали положительные результаты нового игрового построения знаний и повышение осведомленности о методах активного обучения. В целом, большинство участников (80%) полностью согласилось с возможностью применения этой методики в классе с учениками на разных образовательных этапах; столько же педагогов посчитали, что семинар Breakout Edu положительно повлиял на динамику мотивации и командную работу. Несмотря на некоторые ограничения, связанные с размером выборки, наш эксперимент способствует распространению нового подхода, ориентированного на обучающихся. Определение проблем профессионального развития будущих преподавателей CLIL совместимо с задекларированными ООН целями устойчивого развития (цель № 4, Генеральная ассамблея ООН). Полученные в ходе исследования результаты заслуживают тщательного анализа со стороны образовательного сообщества, законодательных органов и преподавателей, занимающихся продвижением CLIL, методик активного обучения и геймификации.